The student report card and the teachers' experience of reporting; more than an addendum to the semester - Long, Susan (Curtin University, 2013)
Report writing is a largely unexamined aspect of professional practice. It would appear to be a simple task of collating marks and writing a summary statement; however, there is evidence that the teacher deeply engages with the task over an extended period of time. It is less an administrative task than an emotionally charged product of multiple judgements, that in turn exposes the teacher to external judgement.This case study presents an exposé of the experience of report writing for teachers in the Australian state of Victoria between 2008 and 2012, a time during which a new curriculum and the Student Report Card were implemented. The new reporting format required teachers to report on performance against curriculum linked Progression Points, work habits and to describe areas of achievement and strategies for improvement.In order to examine the phenomenon of reporting, a multiple stage multi-method research design was devised. It includes a widely distributed questionnaire, a Process Tracing task and then a teacher composed narrative. These three stages fit within a parfocal approach to interpreting the experience of reporting. At each stage of the data collection, the field of view was narrowed but the focus on reporting experiences were maintained. Data collected identified aspects of teacher knowledge, thinking, internal and external contextual influences. A composite description of the experience of reporting was framed using Feldman’s Teaching as a way of being model (1997).The study showed that the teacher constructs the multidimensional knowledge base that understands student learning through interacting in the learning setting over an extended period. The classroom exists within the wider sociocultural context which shapes the judgements made. Sharing the judgements made about learning increases the vulnerability of the person acting in the role of teacher. This study makes a valuable contribution to understanding the knowledge base for teaching, acknowledging its complexity and celebrating the role of relationship in teaching. It may assist experienced teacher to reflect on their reporting strategies to improve the validity of reports. It will make a positive contribution to pre-service teacher training, alerting beginning teachers to the need to prepare for reports over the semester.